L’utilisation du concept polysémique de résilience : une analyse empirique en zone côtière - Idrissa Oumar Kane; Jean-Paul Vanderlinden (VertigO)
Resilience, as a concept, is now widely used for the analysis of adaptation to climate change in coastal areas. This concept is mobilized by many disciplinary fields and it is thus associated to a high variety of meanings and contexts. This article proposes to : (i) conduct an analysis of the use of the concept of resilience in order to understand the scientific, political and social impact that this polisemy has on stakeholders’ discourses and (ii) establish a framework that renders explicit the uses of resilience in a variety of settings. An international multi partnership and highly interdisciplinary project, the THESEUS project, is used as a case study. The main results show : (1) at the scientific level, the uses of the word resilience obey to a paradigmatic logic associated to knowledge production environments, (2) at the policymaking and implementation levels, the variety of meanings generates a risk of instrumentalisation as well as potential conflicts of interests.